PENGARUH KETERDEDAHAN MEDIA KOMUNIKASI TERHADAP KECEPATAN ADOPSI TEKNOLOGI FERMENTASI KAKAO DI KABUPATEN GUNUNG KIDUL - , KARTIKA KUMALA DEWI, Ir. Harsoyo, M.Ext.,Ed. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main objective of the research was to find out influencing factors of cocoa farmers exposure to comunicaton media and cocoa farmers adoption speed. This research was held in Patuk and Ponjong Subdistrict in Gunung Kidul Regency, using survey method. Analysis of this research was done by multiple linier regression. The result indicated that adoption speed average of cocoa farmers in Gunung Kidul Regency is 29.6 years. It means cocoa farmers can fully adopted fermentation technology within 29.6 years. The significant influencing factors of cocoa farmers exposure to communication media are attitude and motivation, then the unsignificant influencing factors are age and education. The significant influencing factors of cocoa farmers adoption speed are attitude, motivation, and experience, then the unsignificant influencing factors are innovation attribute and media exposure.